2015
DOI: 10.1088/1367-2630/17/8/083042
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics in a grand ensemble: Bergmann–Lebowitz model and adaptive resolution simulation

Abstract: This article deals with the molecular dynamics simulation of open systems that can exchange energy and matter with a reservoir; the physics of the reservoir and its interactions with the system are described by the model introduced by Bergmann and Lebowitz (P G Bergmann and J L Lebowitz 1955 Phys. Rev. 99 578). Despite its conceptual appeal, the model did not gain popularity in the field of molecular simulation and, as a consequence, did not play a role in the development of open system molecular simulation te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 52 publications
1
105
0
Order By: Relevance
“…In this study we employ the Grand Canonical Adaptive Resolution Simulation Scheme (GC-AdResS) for molecular dynamics [25,26,[28][29][30]38]. Two regions of a simulation box having different resolution regions: 1. atomistic (AT) and 2. a coarse-grained (CG) system can be linked using this multi-resolution simulation method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we employ the Grand Canonical Adaptive Resolution Simulation Scheme (GC-AdResS) for molecular dynamics [25,26,[28][29][30]38]. Two regions of a simulation box having different resolution regions: 1. atomistic (AT) and 2. a coarse-grained (CG) system can be linked using this multi-resolution simulation method.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that models that can reproduce macroscopic thermodynamic quantities such as density and temperature can be used as coarse-grained models, so that AdResS is re-framed within the Grand Ensemble idea of open boundary systems [29,30,38]. In this work, we use a spherical atomistic region of radius d at that is surrounded by a hybrid region of width d hy .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AdResS is re-framed within the Grand Canonical approach 28,29 , or even further, within the more general Grand Ensemble idea of open boundary systems 30,31,38 . For the specific study in this work, the atomistic region is modelled as a sphere of radius d at and is surrounded by a spherical hybrid region of width d hy and the remainder of the box is the CG region that serves as a particle reservoir for the AT region; see the pictorial representation in Fig Within the AT and CG regions the force acting between two molecules is derived from the respective potentials.…”
Section: Cg αβmentioning
confidence: 99%
“…In present work, in particular, we employ classical molecular dynamics within the context of the Adaptive Resolution Simulation approach (AdResS) 26,27 in its Grand Canonical version (GC-AdResS) [28][29][30] .…”
mentioning
confidence: 99%